2007
DOI: 10.4304/jcp.2.2.25-36
|View full text |Cite
|
Sign up to set email alerts
|

Defending Cyberspace with Fake Honeypots

Abstract: Abstract-Honeypots are computer systems designed for no purpose other than recording attacks on them. Cyber-attackers avoid them since honeypots jeopardize the secrecy of attack methods and it is hard to launch attacks from them. This suggests that a computer system might pretend to be a honeypot to scare away attackers, reducing the number of attacks and their severity. This could be done on ordinary computer systems as a kind of "vaccination" of those systems, to create what we call "fake honeypots". After s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…She can disguise normal systems as honeypots and honeypots as normal systems. Rowe et al [2] showed that this technique effectively enhances computer network security. After the network is created, an attacker then attempts to compromise systems.…”
Section: The Deception Gamementioning
confidence: 99%
See 3 more Smart Citations
“…She can disguise normal systems as honeypots and honeypots as normal systems. Rowe et al [2] showed that this technique effectively enhances computer network security. After the network is created, an attacker then attempts to compromise systems.…”
Section: The Deception Gamementioning
confidence: 99%
“…Attackers require additional resources (e.g., time, money) to comprehend the situation and to tailor their attacks to the specifics that the situation demands. Deception has a long history of effective use within the military and is now being deployed for the protection of information systems [1], [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deception through gameplay has been discussed [31,11,8,37], or implemented by hand [10], but little empirical work has been done to demonstrate the usefulness such an approach provides. Prior work traditionally focuses on improving information gain generated by honeypots [37,8] us- Figure 5: Numbers of components for G dnsw and G null for each day of the long-term experiment.…”
Section: Related Workmentioning
confidence: 99%